The Relationship Of Eye Care Compliance With Iris Inflammation In Patients Post Phacoemulsification Surgery - Suhartini; Anik Nuridayanti; Nurhidayah (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
Iris inflammation can occur in post cataract surgery patients due to lack of adherence to post cataract surgery care. With the occurrence of inflammation of the iris will cause discomfort to patients with complaints of redness of the eyes, blurred vision, and pain in the eyes. The purpose of this study was to determine the relationship between eye care adherence and iris inflammation in postoperative phacoemulsification patients at Undaan Eye Hospital Surabaya. The study used an analytical survey design with a cross sectional approach. The sample of this study was 80 people who were examined on the seventh day after Phacoemulsification surgery taken by purposive sampling. The independent variable in this study was eye care compliance and the dependent variable was the incidence of iris inflammation. Data were collected through observation and questionnaires. Data analysis using chi-square test. The results showed that the level of adherence to eye care in post-phacoemulsification patients was mostly very compliant with 60 respondents (75%), a small proportion of respondents experienced inflammation as many as 19 respondents (23.8%). The results of data analysis using the chi square test was 57.728 with a p value of 0.000 <0.05, which means that there is a relationship between eye care compliance and the incidence of iris inflammation in post-operative phacoemulsification patients. The conclusion is that the success of cataract treatment cannot be separated from postoperative care. Postoperative care adherence is an important factor in the success of cataract surgery recovery. It is hoped that this research can motivate nurses to always provide education to be more obedient to postoperative phacoemulsification care and patients care about health, especially compliance in postoperative phacoemulsification care.